Phellinus Linteus Extract Sensitizes Advanced Prostate Cancer Cells to Apoptosis in Athymic Nude Mice - Tsuji, Takanori (Public Library of Science, 2010)
Phellinus linteus (PL) mushroom possesses anti-tumor property. We previously reported that the treatment with PL caused cultured human prostate cancer cells to undergo apoptosis. To further studying the mechanisms of PL-mediated apoptosis, we performed xenograft assay, together with in vitro assays, to evaluate the effect of PL on the genesis and progression of the tumors formed from the inoculation of prostate cancer PC3 or DU145 cells. After the inoculation, nude mice were injected with PL every two days for 12 days. Although PL treatment did not prevent the formation of the inoculated tumors, the growth rate of the tumors after PL treatment was dramatically attenuated. We then tested the effect of PL on the tumors 12 days after the inoculation. After inoculated tumors reached a certain size, PL was administrated to the mice by subcutaneous injection. The histochemistry or immunochemistry analysis showed that apoptosis occurred with the activation of caspase 3 in the tumors formed by inoculating prostate cancer DU145 or PC3 cells. The data was in a good agreement with that from cultured cells. Thus, our in vivo study suggests that PL not only is able to attenuate tumor growth, but also to cause tumor regression by inducing apoptosis.